(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
These days, LGBT rights have become an important issue. In many regions, this group of people is deprived of basic human rights. Though much debate have been taking place across the globe, lesbian, gay, bisexual, and transgender (LGBT) individuals are deprived of even the basic human rights in many parts of the world. Though several governments have come forward proactively and implemented systems ensuring all human rights to this group of individuals, the issues still looming large. LGBT people face discrimination in different ways in many societies. Abuse, physical and psychological tortures and state-sponsored execution for showing different sexual orientation are quite common in many countries. Thus, the most pressing problem is the criminalization of LGBT people. For the violations of human rights, there are laws that the governments or appropriate authorities can implement to punish the offenders. Violence and abuse that the LGBT people face these days is a contentious issue today. In this research study, we explore violence against the LGBT community and different health issues they face in details.